O educador social em uma institui????o socioeducativa no Distrito Federal: atribui????es, perfil e expectativas - Moreira, Maria Jos?? Thomaz (2016)
The aim of this research is to analyze the social educator in a social-educative institution and his pedagogic practice set by the institution. It also aims to identify the educator???s profile; to recognize his features by keeping up with his assignments closely. Lastly, the aim is to identify the need concerning the educator???s professional background in order to better approach the pupil. This research is focused on the educator; an educational agent figure well acknowledged worldwide, it is though still unknown in Brazil. The research took place in Ceil??ndia, in an NGO which promotes culture and peace; this institution aims to support the pupils and to prevent them from vulnerability and social risk. The goal is to insert them into the society. The research intends to contribute to the educator???s professional consolidation from resources offered by the Catholic University of Brasilia, supported by the Youth, Education and Society UNESCO cathedra, which is engaged to spread of Human rights and to promote social inclusion in their projects. That given study is qualitative focused on the studied group, which was given a questionnaire. The study has its foundation on researches already done by authors of Social pedagogy, focusing the practice on the professional. Social pedagogy is a scientific issue, which will provide Social Education with tools, it is practice. However, one is connected to the other even when they differ discursively (Pedagogy) in order to attempt to a support in practice (Education). It is about setting professional spot and discourse; they harmonize with the social view. Among the results acquired are the educator???s assignment at the institution, this is reigned by Dom Bosco???s principles and is in line with Children???s law, those institutions work together in order to develop the pupil. The research made it able to comprehend the educator???s thought on a NGO, Who they are, what they want. Social educators show a profile that accentuates some qualities such as human sensitivity, perseverance, empathy, religious nature of inspiration. The most significant assignments relate to the need to define their roles and positions, the ability to solve problems, using new technologies and adapt to new environments. They manifest expectations of an improvement course in socio-educational area that meets the academic needs improvement, which has a philosophical line based on the principles of Don Bosco education, and deepen preventive education.